Analisa Kepuasaan Pelanggan dalam Layanan Jasa Travel and Tour pada PT. Denar Pesona Menggunakan Metode Fuzzy Servqual - Nandang Iriadi; Priatno Priatno; Putri Agnes Sulistia (Universitas Bumigora, 2019)
Companies like these services are important to improve the quality of services provided to customers. In this case it is very useful for companies to plan ahead. For this reason, PT. Enchantment Denar has a different way to assess customer satisfaction. In practice, the activity of evaluating the level of customer satisfaction must be done with a good and appropriate method. Fuzzy Servqual method was chosen to assess and rank the level of customer satisfaction. This study aims to determine the level of customer satisfaction with the services of PT. Enchantment Denar and analyze service factors that must be improved and quality improved. The results of the study show that the gap value is negative, it can be said that the services provided by PT. Denar Charm has not satisfied the customer's heart. Then the lowest result of the gap is -0.334 of the empahty variable and the highest result is -1.137 in the responsiveness variable. Therefore PT. Enchantment Denar must further increase the lack of results so that in the future PT. Denar Charm is very good service for the customer.